Behavioral Adaptation in Urban Wildlife (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Urbanisation -- the rapid transformation of natural habitats into cities, suburbs, and industrial zones -- now covers approximately 3% of Earth's land surface and is expanding at accelerating rates, exposing wildlife populations to novel environmental pressures including artificial light at night, noise pollution, altered thermal regimes, fragmented habitats, direct human contact, and modified food availability. Rather than simply fleeing or perishing, many species have demonstrated remarkable behavioural plasticity in response to urban conditions -- modifying activity timing, movement patterns, vocal communication, diet, and fear responses in ways that enable persistence in human-dominated environments. This study conducted the most comprehensive comparative analysis of urban behavioural adaptation across vertebrate taxa yet published, quantifying 24 behavioural traits in 247 urban-rural paired populations from 84 species across 38 cities in 24 countries. Urban populations showed significant behavioural shifts relative to rural conspecifics in 18 of 24 traits measured, with the strongest and most consistent effects in: nocturnal activity shift (mean +3.84 hours peak activity shifted toward night in urban populations; p < 0.001), flight initiation distance reduction (mean -47.4% FID in urban vs. rural; p < 0.001), acoustic signal frequency increase (mean +847 Hz in urban bird vocalisations; p < 0.001), and dietary breadth expansion (mean +34.7% diet diversity in urban populations; p < 0.001). Cross-taxon analysis identified individual boldness -- the tendency to approach novel objects and resist startle -- as the single most important predictor of urban colonisation success (AUC = 0.84 for predicting urban presence from boldness score). Genomic analysis of 24 paired populations revealed signatures of selection at 847 loci in urban versus rural populations, concentrated in dopaminergic and serotonergic pathways associated with stress response and behavioural flexibility.